HAVING A VARIETY OF ACTIVITIES MAKES THE MUSEUM MORE ATTRACTIVE TO VISITORS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, April 2015 Mention the word ‘museum’ and what comes to mind would be a place where various artifacts and historical items are kept. By looking at the museum visits, they would be synonymous mostly with classroom trips by primary and secondary school students.